A Rare Case of Septic Shock Secondary to Emphysematous Hepatitis - Nada, Khaled M. (Case Rep Crit Care, 2017)
OBJECTIVE: To describe a case of emphysematous hepatitis which is a rare clinical entity, characterized by a fatal, rapidly progressive infection of the liver with a radiological appearance simulating emphysematous pyelonephritis and to help provide more data about the causative organisms and precipitating factors of this pathology. DATA SOURCES AND SYNTHESIS: Relevant literature was reviewed and, to the best of our knowledge, there is limited data regarding the pathogenesis, causative organisms, and management of this condition. CONCLUSION: Emphysematous hepatitis is a rapidly progressive infection that can be fatal in the absence of appropriate therapeutic intervention. Initial clinical manifestations are usually subtle and thus high clinical suspicion is required for early diagnosis and management of this condition to help decrease the mortality rates.